Interrogating calls for increased national service: A political discourse analysis - Rost-Banik, Colleen; Perrotti, Carmine (Journal of Praxis in Higher Education, 2024)
Service-learning and other forms of civic and community engagement have flourished within U.S. higher education over the past three decades, in part, through formal political processes to advance the national, economic, cultural, social, and youth development purposes of higher education. In this article we examine two recent national reports—one from academia and one from the federal government—that call for expanding civic education and national service within higher education. Findings illuminate the ways in which political discourse is used to frame national crises that then conjure a social imaginary wherein specific policy and practices of civic education and national service are justified. We argue that this not only conceals what types of political actions are possible, but also determines parameters of eligibility for who receives the resources necessary for survival. The reports under investigation have profound implications, further tethering higher education to U.S. nationalism and imperialism.